The Wednesday wars - Schmidt, Gary D. (New York Scholastic, 2007)
During the 1967 school year, on Wednesday afternoons when all his classmates go to either Catechism or Hebrew school, seventh-grader Holling Hoodhood stays in Mrs. Baker's classroom where they read the plays of William Shakespeare and Holling learns much of value about the world he lives in.
Companion to: Okay for now.
Newbery Honor, 2008.
Keywords: Shakespeare, William -- 1564-1616 -- Fiction; Coming of age -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Family life -- New York (State) -- New York -- Fiction; Long Island (N.Y.) -- History -- 20th century -- Fiction